Implementasi UU SISDIKNAS dalam Kebijakan Integrasi Kurikulum Pendidikan Islam di SDIT Sunan Averroes Sleman - Antin Rista Yuliani; Suwadi Suwadi (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2023)
The purpose of this research is to analyze the implementation of the SISDIKNAS law in Islamic education policy through integrated education to answer the problem of educational dichotomy. This research uses field research and qualitative descriptive research. The location of this research was at SDIT Sunan Averroes Sleman. The research informants were school principals, teachers, and students' parents. Data collection techniques through observation, interviews, and documentation. Test the validity of the data through source triangulation and technique triangulation. Data analysis through data collection, data reduction, data presentation, and drawing conclusions. The results of this study are that the implementation of the SISDIKNAS Law in the Islamic education curriculum policy has been explicitly regulated as a subject, namely in article 37 of the 2003 SISDIKNAS Law, the Implementation of the SISDIKNAS Law in the integration policy of Islamic education curriculum at SDIT Sunan Averroes Sleman, among others 1) The SISDIKNAS Law is used as a guideline in preparing curriculum policies, 2) The subject matter at SDIT is in accordance with the subject matter in Article 37 of the SISDIKNAS Law and there are plus points in the field of religion, 3) The curriculum policy at SDIT integrates general knowledge and religion as a solution to the problem of educational dichotomy, 4) Content Islamic Religious Education material in Integrated Islamic Schools is not branched so it does not burden children, 5) Compilation of curriculum with planning, implementation and evaluation processes. Supporting factors for the implementation of the SISDIKNAS Law in the policy of integrating Islamic education at SDIT Sunan Averroes Sleman are teachers who are still young, whose minds are energetic, each class does not go to formal classes so that learning runs more optimally, and parental support. While the inhibiting factors are the teacher's educational background which is not linear and the limited infrastructure.Â Kata kunci: SISDIKNAS Law, Islamic Education Policy, Integrated Islamic Schools